Peculiarities of Protection of Rights and Interests of Heirs: Theoretical Aspects - Zaika, Yuri O.; Kukhariev, Oleksandr Ye.; Skrypnyk, Volodymyr L.; Mytnyk, Aliesia A. (International Journal of Criminology and Sociology, 2021)
The relevance of this study is due to the necessity to ensure the proper exercise of subjective civil rights in the field of inheritance law. Protection in inheritance is related to the general right to protection. Due to the peculiarities of inheritance law as a sub-branch of civil law, it has its own specifics, which is manifested primarily in the definition of special ways to protect violated unrecognized or challenged rights. In addition, the protection of the rights of heirs takes place only within the inheritance relationship, which is characterized by a long nature. The purpose of the article is to identify the features of protection of subjective civil rights of heirs in the field of inheritance. This necessitates the use of special methodological approaches that will identify the characteristics of protection of the rights of heirs, as well as research methods such as dogmatic, formal-logical, systematic, comparative law. The article analyses the recognition of the right of ownership of inherited property in court and proves that this exceptional method of protection is used if there are obstacles to the notarization of inheritance rights. The most typical and widespread special ways to protect the rights of heirs are considered: removal from the right to inherit, invalidation of the will, change of the order of obtaining the right to inherit, reduction of the size of the obligatory share in the inheritance. The outlined issues were not widely covered in the legal literature, as the attention of scholars was mainly in the perspective of clarifying the legal nature of protection and defence, the ratio of forms and methods of protection of subjective civil rights, analysis of general methods of protection of subjective civil rights. That is why this work is an important contribution to outlining the issue of inheritance law and attracting due attention of the scientific community.